[PP.35.17]: EFFECT OF 3-MONTH TREATMENT WITH HYPOTENSIVE DRUGS ON MINERALS AND RELATED PARAMETERS IN PATENTS WITH HYPERTENSION. (June 2015) - Pupek-Musialik>, D.>; Suliburska, J.; Szulinska, M.; Musialik, K.; Lis, I.; Stempien, M.; Bogdanski, P.
Abstract : Objective: The aim of this study was to evaluated the influence of monotherapy with hypotensive drugs on iron and copper status and related parameters in newly diagnosed patients with hypertension. Design and method: Ninety eight patients, mean aged 53.6 ± 13.7 years with diagnosed essential hypertension, beginning monotherapy treatment with diuretics (36 subjects), calcium antagonists (18 subjects), beta-blockers (18 subjects), angiotensin converting enzyme inhibitors (14 subjects), angiotensin II receptor antagonists (12 subjects) were employed in the study. Over three months, the patients underwent monotherapy. Iron and copper concentration in serum, erythrocytes, urine and hair were determined using flame atomic absorption spectrometry. Concentration of catalase (CAT), superoxide dismutase (SOD) were assayed in serum with diagnostic kits (Oxis). Ferritin and ceruloplasmin were measured in serum using immunoenzymatic method. Red blood cells, hemoglobin and hematocrit were determined in whole blood. Results: Significant decreased in CAT and SOD after hypotension treatment with all group of analyzed drugs were found. The lower concentration (not markedly) of hemoglobin in blood after treatment was also observed. The hypotensive drugs did not influence on iron and copper status. Conclusions: In conclusion, hypotensive treatment should include monitoring of CAT and SOD concentration in hypertensive patients.